Cerebral cysticercosis in a wild Bengal tiger (Panthera tigris tigris) in Bhutan: A first report in non-domestic felids. (April 2021) - Phuentshok, Yoenten; Choden, Kinley; Alvarez Rojas, Cristian A.; Deplazes, Peter; Wangdi, Sonam; Gyeltshen, Kuenzang; Rinzin, Karma; Thapa, Nirmal Kumar; Tenzinla, Tenzinla; Dorjee, Dechen; Valitutto, Marc; Gilbert, Martin; et al.
Abstract: The endangered Bengal tiger ( Panthera tigris tigris ) is a keystone species playing an essential role in ecology as well as in the social and spiritual lives of the Himalayan people. The latest estimate of the Bengal tiger population in Bhutan accounts for 103 individuals. Infectious organisms, including zoonotic parasites causing high burden in human health, have received little attention as a cause of mortality in tigers. Taeniosis/cysticercosis, caused by the cestode Taenia solium, is considered one of the major neglected tropical diseases in Southeast Asia. We present here a case of neurocysticercosis in a Bengal tiger showing advanced neurological disease outside Thimphu, the capital city of Bhutan. After palliative care, the animal died, and necropsy revealed multiple small cysts in the brain. Here we show the presence of two genetic variants of T . solium in the parasite material collected based on PCR and sequencing of the complete cox1 and cytB genes. The sequences form a discrete branch within the Asia plus Madagascar cluster of the parasite. On other hand, tests for feline morbillivirus, feline calicivirus, canine distemper virus, Nipah, rabies, Japanese encephalitis, feline leukaemia and feline immunodeficiency virus were negative. In contrast, PCR for feline herpesvirus was positive and a latex agglutination test revealed an elevated antibody titer against Toxoplasma gondii (titer 1:256). The molecular examination of taeniid eggs isolated from the tiger faeces produced sequences for which the highest homology in GenBank is between 92% and 94% with T. regis and T. hydatigena . This fatal case of T. solium neurocysticercosis, a disease previously unrecorded in tigers or other non-domestic felids, demonstrates an anthropogenically driven transmission of a deadly pathogen which could become a serious threat to the tiger population. Graphical abstract: Image 1 Highlights: This is the first report of a fatal infection with Taenia solium in a Bengal tiger. There is a need for research into infectious disease threats to tigers in Bhutan. The importance of a 'One Health' approach is demonstrated and recommended. Non-domestic felids.